A Novel Salt-Bridge Electroflocculation Technology for Harvesting Microalgae - Hou, Yuyong; Liu, Chenfeng; Liu, Zhiyong; Han, Tong; Hao, Nahui; Guo, Zhile; Wang, Weijie; Chen, Shulin; Zhao, Lei; Safavi, Maliheh; Ji, Xiang; Chen, Fangjian (Frontiers in Bioengineering and Biotechnology, 2022)
Microalgae biomass, as a promising alternative feedstock, can be refined into biodiesel, pharmaceutical and food productions. However, harvesting process for quality biomass still remains a main bottleneck due to its high energy demand. In this study, a novel technique integrating alkali-induced flocculation and electrolysis, named salt-bridge electro-flocculation (SBEF) with non-sacrificial carbon electrodes was developed to promote recovery efficiency and cost savings. The results showed that the energy consumption decreased to 1.50 Wh/g biomass with the high harvesting efficiency of 90.4% under 300 mA in 45 min. The mean particle size of algae flocs increased 3.85-fold from 2.75 to 10.59 µm, which was convenient to the follow-up processing. Another major advantage of this method is that salt-bridge firmly prevented cells being destroyed by anode’s oxidation and did not bring any external contaminants to algal biomass and flocculated medium, which conquered the technical defects in electro-flocculation. The proposed SBEF technology could be used as a low cost process for efficient microalgae harvest with high quality biomass.